Efficacy of Intravenous, Endotracheal, or Nasal Adrenaline Administration During Resuscitation of Near-Term Asphyxiated Lambs - Songstad, Nils T.; Klingenberg, Claus; McGillick, Erin V.; Polglase, Graeme R.; Zahra, Valerie; Schmölzer, Georg M.; Davis, Peter G.; Hooper, Stuart B.; Crossley, Kelly J. (Frontiers in Pediatrics, 2020)
Objectives: Neonatal resuscitation guidelines recommend administering intravenous (IV) adrenaline if bradycardia persists despite adequate ventilation and chest compressions (CC). Rapid IV access is challenging, but little evidence exists for other routes of administration. We compared IV, endotracheal (ET) and intranasal routes for adrenaline administration during resuscitation of asphyxiated newborn lambs. Study design: Near-term lambs (n=22) were delivered by caesarean section. Severe asphyxia was induced by clamping the umbilical cord while delaying ET-ventilation until carotid artery blood flow ceased. Following a 30 s sustained inflation and ventilation for 30 s, we commenced uncoordinated CC at 90/min. We randomised four groups receiving repeated treatment doses (Td) every 3rd minute of i) IV-Adrenaline (50 µg), ii) ET-Adrenaline (500 µg), iii) nasal-Adrenaline via an atomizer (500 µg) and iv) IV-saline. If return of spontaneous circulation (ROSC) was not achieved after three Tds by the assigned route, up to two rescue doses (Rd) of IV adrenaline were administered. Main outcome measures were achievement of ROSC and time from start of CC to ROSC, defined as heart rate >100/min, and mean carotid arterial pressure > 30 mmHg. Results: In the IV-Adrenaline group, 5/6 lambs achieved ROSC after the first Td, whereas 1 lamb required two Tds before achieving ROSC. In the ET-Adrenaline group, 1/5 lambs required one Td, 1 lamb required three Tds, 2 lambs required 2 Rds and 1 did not achieve ROSC. In the Nasal-Adrenaline group, 1/6 lambs required one Td, 2 required two Tds, whereas 3 lambs required either one (2 lambs) or two (1 lamb) Rds of adrenaline to achieve ROSC. In the IV-saline group, no lambs achieved ROSC until adrenaline Rds; 4/5 lambs required one Rd and 1 lamb required two Rds. Time to ROSC was shorter using IV-Adrenaline (2.4  0.4 minutes) compared with the ET-Adrenaline (10.3  2.4 minutes), Nasal-Adrenaline (9.2  2.2 minutes) and IV-saline (11.2  1.2 minutes). Conclusion: IV adrenaline had superior efficacy compared to nasal or ET administration. Nasal administration had similar effect as ET administration and is an easier route for early application. Nasal high-dose adrenaline administration for neonatal resuscitation merits further investigation.